RANCANGAN APLIKASI PENCARIAN JALUR TERPENDEK DENGAN PENDEKANAN GEOGRAPHIC INFORMATION SYSTEMS DAN DIJKSTRA'S ALGORITHM - Edy Nasri; Ahmad Alwani (Jurnal Ilmiah Sains dan Teknologi, 2021)
Islamic boarding schools play a role in developing the independent character of students, however, in addition to the large role of boarding schools, there are still many obstacles, namely the difficulty of obtaining accurate information about the existence of boarding schools. Currently, to obtain information about Islamic boarding schools in Pandeglang Regency, they still use conventional methods, like coming directly to the location of the boarding school. There are even some boarding schools whose information cannot be found, so we need a solution to solve these problems by utilizing information technology and computers. Researchers offer a solution to overcome this problem by utilizing information system technology, namely Geographic Information Systems by utilizing Google Maps as a map provider and Dijkstra's Algorithm as a method to find the shortest path from one point to another on a graph. This research produces a digital map application on the web by utilizing the Google Maps API and Web Service using the Apache Web Server to retrieve data from the MySQL database.The goal to be achieved in this research is to build a Geographic Information System (GIS) for boarding schools that can be used to provide information about the map of the location of boarding schools in the Pandeglang Regency area along with other supporting information in the boarding schools.